Avaliação da atividade antioxidante de diferentes classes de compostos contra a oxidação de lipoproteínas de baixa densidade - Portella, Rafael de Lima (2011)
Abnormalities of lipid metabolism often lead to pathologic lipid accumulation in the vessel wall, oxidative and chronic inflammatory sequelae and the formation of atherosclerotic lesions, ultimately leading to clinical events. Low density lipoprotein (LDL) oxidative modification in the vascular wall seems to be a key factor in atherosclerosis development. Following the oxidation hypothesis of atherosclerosis the role of antioxidants has been investigated in a large number of epidemiological, clinical and experimental studies. Therefore, we investigated the antioxidant activity of three compounds of different classes in preventing the low density lipoprotein oxidation. In the guaraná study, we showed that subjects who habitually ingested guaraná (GI) demonstrated lower conjugated dienes production than did subjects who never ingested guaraná (NG; reduction of 27%, p < 0,0014), independent of other variables. However, in the GI group the conjugated dienes production was positively associated with glucose levels. The GI group also showed a total cholesterol level significantly lower than NG group. Also, guaraná demonstrated a high antioxidant activity in vitro, mainly at concentrations of 1 and 5 μg/mL, demonstrated by suppression of CDs and TBARS productions, tryptophan destruction and high TRAP activity. Guaraná, similar to other foods rich in caffeine and catechins such as green tea, has some effect on LDL oxidation that could partially explain the protective effects of this food in cardiometabolic diseases. In the thiosemicarbazone study, salicylaldehyde-4- phenylthiosemicarbazone (SPTS) may have antioxidant activity against Cu2+- and 2,2′- Azobis(2-methylpropionamidine) dihydrochloride (AAPH)-induced LDL and serum oxidation. Additionally, SPTS was effective at preventing tryptophan destruction. SPTS also showed significant total radical-trapping antioxidant activity and could prevent thiobarbituric acid reactive substances (TBARS) formation induced by sodium nitroprusside in different rat tissues and by Cu2+ in human LDL and serum. These results indicate that the antioxidant effect of SPTS is caused by a combination of transition metal chelation and free-radicalscavenging activity. In the organotellurium study, the 2-phenyl-2-tellurophenyl vinylphosphonate (DPTVP) may have antioxidant activity against Cu2+- and 2,2′-azobis(2- methylpropionamidine) dihydrochloride (AAPH)-induced LDL and serum oxidation. Additionally, DPTVP was effective at preventing tryptophan oxidation. DPTVP also showed significant total radical-trapping antioxidant activity and could prevent thiobarbituric acid reactive substance (TBARS) formation induced by Cu2+ in human LDL and serum. Additionally, DPTVP exhibited no toxicity in rat aorta slices. The results presented here indicate that the antioxidant effect of DPTVP is caused by a combination of free-radicalscavenging activity and possible blockade of the copper binding sites of LDL. Considering these preliminary results, we can conclude that the three compounds presented a potential antioxidant activity and could prevent the oxidative modifications of LDL. These data encourage us to evaluate these compounds in in vivo studies and investigate additional properties in preventing the atherogenic process.